ÍNDICES REPRODUCTIVOS DE ALPACAS HUACAYA DEL INIA QUIMSACHATA 1997 – 2012 – PUNO - PERÚ - Huanca Mamani, Teodosio; Mamani Cato, Rubén Herberht; Naveros Flores, Mary Luz; Apaza, Nolberto (Universidad Nacional del Altiplano - Puno, 2021)
4 páginas